ANALISIS LAPORAN KEUANGAN PENJUALAN PADA USAHA MAKARONI “KRIUKZZ” - Fahmi Syahrian; Rizqi Putra Ramadhan; Dena dwi Rohmagin; Nur Alfi Faroha; Ovin Liviana Bela; Hendra Dwi Prasetyo (Jurnal Bina Bangsa Ekonomika, 2022)
In writing accounting statements in the field of business which on actually simple, but always doing business always applying the rules that apply in the administration of existing financial standards. The Indonesian Agency of Accountants already has SAK-EMKM which was established in early 2018 this broken up business actors to compile financial statement. Writing this article aims to compile financial reports on the Student Entrepreneurship Program in the Makaroni Kriukzz business based on SAK_EMKM. In writing this article used qualitative, where the conclusions of article tell that PKM on in it KRIUKZZ business. In can be said result in financial statements on PKM it the Kriukzz business consist of financial statements, profit and loss statements and notes on financial statements